Toxoplasma gondii seroprevalence in rheumatoid arthritis patients treated with biological agents - İnal, Ali and Taş, Dilaver (Journal of Surgery and Medicine, 2019)
Aim: Toxoplasma gondii infection appears to be asymptomatic in most of the patients but its mortality rate is high in immunocompromised patients and in those taking immunosuppressive drugs, when reactivated and untreated. Severe infections are well-known to occur in rheumatoid arthritis (RA) patients treated with immunosuppressive drugs such as tumor necrosis factor alpha antagonist. TNF-alpha is essential for granuloma formations, which are important for the defense against intracellular pathogens and the process. It seems it is inevitable that anti-TNF agents being used in RA disease treatment are going to create an incline towards all kind of infections, especially tuberculosis and other granulomatous infections (toxoplasmosis, histoplasmosis, etc.). We investigated the T. gondii seroprevalence in RA patients treated with biologic agents and disease modifying anti-rheumatic drugs, systemic lupus erythematosus patients treated with immunosuppressive drug combinations and compared them with healthy controls. Methods: In this study we investigated the T. gondii seroprevalence in 33 rheumatoid arthritis (RA) patients treated with biologic agents, 26 RA patients treated with disease modifying anti-rheumatic drugs (DMARD), 15 Systemic lupus erythematosus (SLE) patients treated with immunosuppressive drug combinations and in 19 healthy controls. Results: Toxoplasma IgM enzyme linked immunosorbent (ELISA) assay was negative for all groups. Whereas 29 (87.9%) of rheumatoid arthritis patients treated by the biologic agents, 21(80.8%) of rheumatoid arthritis patients treated by disease modifying antirheumatic drugs, 15 (100%) of Systemic lupus erythematosus patients and 4 (21.1%) of the controls were seropositive for Toxoplasma Ig G. Conclusion: During the immunosuppressive treatment the risk of toxoplasma infection should be taken into consideration.